A case report of Dystocia in a primiparous West African dwarf ewe due to relative fetal oversize associated with poor mating management practices in Ibadan, Nigeria (2019)
A one and a half (1½) year old Primiparous West African dwarf ewe, weighing 12 kg was presented with history of anorexia and straining of about 24 hours duration to the University of Ibadan Veterinary Teaching Hospital, Ibadan. Close observation of the animal showed a narrow birth canal with bilateral carpal flexion of the foetus which also appeared too big for the dam. Rectal temperature was 36.9°C, Heart rate was 68beats per minute and respiratory rate was 36 breathes per minute. The dam was reported to be mated with a ram of same breed weighing 40kg. Dystocia was diagnosed and caesarean section was recommended to relieve the dystocia. The right lateral side of the abdomen close to the Paralumbar fossa was carefully and aesthetically shaved and prepared. Induction of anaesthesia was done using 2 ml of Lignocaine given epidurally as an inverted L-block and 1 ml of Duracaine was given posteriorly. Complete desensitization of the region was achieved within 5minutes of induction. Drapes were used to prevent contamination as much as possible. A small straight 10cm long incision was made on the lateral side with no obvious bleeding observed. The uterus was located and incised with the apparently big dead foetus weighing 2.2kg taken out and chromic catgut size 1 was used to suture the uterus. The skin was about to be sutured with nylon suture material when the dam passed on. This report highlighted the detrimental effect of poor reproductive management practices and the delay in seeking veterinary care leading to maternal and fetal death with its grave economic consequences.